2011
DOI: 10.1111/j.1348-0421.2011.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between single nucleotide polymorphism of interleukin-18 and susceptibility to pulmonary tuberculosis in the Chinese Han population

Abstract: Worldwide, M.tb infects more humans than any other single bacterial agent. The World Health Organization estimates there are 8-9 million new cases of clinical TB and 2 million deaths resulting from this disease every year (1). One third of the world's population is infected by M.tb but only about 10% of those infected develop clinical disease (2), which suggests that host genetic factors play a role in TB susceptibility. Therefore, it is important to identify and elucidate the genetic background and factors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
(30 reference statements)
0
21
2
Order By: Relevance
“…Carriage of the variant allele in IL18-607 conferred an almost 4-fold increased risk of developing an IRD event in Indian patients, but had no effect in Cambodians. No such association was observed in a cohort of HIV-negative Indian pulmonary TB patients [7], but in a Han Chinese pulmonary TB cohort without HIV, carriage of the variant allele in IL18-607 was associated with a decreased risk of developing TB [6].…”
Section: Discussionmentioning
confidence: 86%
“…Carriage of the variant allele in IL18-607 conferred an almost 4-fold increased risk of developing an IRD event in Indian patients, but had no effect in Cambodians. No such association was observed in a cohort of HIV-negative Indian pulmonary TB patients [7], but in a Han Chinese pulmonary TB cohort without HIV, carriage of the variant allele in IL18-607 was associated with a decreased risk of developing TB [6].…”
Section: Discussionmentioning
confidence: 86%
“…[16] Ben-Selam et al [17] reported a significant association between active tuberculosis and RANTES gene 28C/G and 403G/A polymorphisms in a Tunisian population. Han et al [18] also found that IL-18 gene polymorphism was more frequent in patients with tuberculosis in the Chinese population. Hahn [19] found a signifi cant relationship between COPD and C. pneuominia infections.…”
Section: Discussionmentioning
confidence: 93%
“…Three SNPs in the promoter of the IL-18 gene at positions −656 G/T, −607 C/A and −137 G/C have been identified. These promoter SNPs have been implicated as susceptibility loci for various diseases, including asthma [22], pulmonary tuberculosis [23], inflammatory bowel disease [24], Parkinson’s disease [25], polycystic ovary syndrome [26], type I diabetes [27], and allergic disorders [28]. …”
Section: Discussionmentioning
confidence: 99%